Progress in understanding electro‐mechanical signalling in the myometrium. (23rd December 2014) - Wray, S.; Burdyga, T.; Noble, D.; Noble, K.; Borysova, L.; Arrowsmith, S.
Abstract In this review, we give a state‐of‐the‐art account of uterine contractility, focussing on excitation–contraction (electro‐mechanical) coupling (ECC). This will show how electrophysiological data and intracellular calcium measurements can be related to more modern techniques such as confocal microscopy and molecular biology, to advance our understanding of mechanical output and its modulation in the smooth muscle of the uterus, the myometrium. This new knowledge and understanding, for example concerning the role of the sarcoplasmic reticulum (SR), or stretch‐activated K channels, when linked to biochemical and molecular pathways, provides a clearer and better informed basis for the development of new drugs and targets. These are urgently needed to combat dysfunctions in excitation–contraction coupling that are clinically challenging, such as preterm labour, slow to progress labours and post‐partum haemorrhage. It remains the case that scientific progress still needs to be made in areas such as pacemaking and understanding interactions between the uterine environment and ion channel activity.